Early Screening of Visual Processing Dysfunctions in Children Born Very or Extremely Preterm - Kooiker, Marlou J. G.; van Gils, Maud M.; van der Zee, Ymie J.; Swarte, Renate M. C.; Smit, Liesbeth S.; Loudon, Sjoukje; van der Steen, Sanny; Reiss, Irwin K. M.; Pel, Johan J. M.; van der Steen, Johannes (Frontiers in Human Neuroscience, 2021)
Introduction Children with early brain damage or dysfunction are at risk of developing cerebral visual impairment (CVI), including visual processing dysfunctions (VPD), which currently remain largely undetected until school age. Our aim was to systematically screen for possible VPD in children born very or extremely preterm from 1 year to 2 years corrected age (CA) and to evaluate the effectiveness of early referral. Method We included N=48 children born <30 weeks from 1y CA. They underwent a two-step VPD screening based on 1) neurological signs indicative of visual brain damage evaluated by neonatologists and/or pediatric neurologist and 2) a functional assessment of visual orienting functions (VOF) with an eye tracking-based test. If at least one of these assessments was abnormal for their age, the children were classified as a risk of VPD and referred to undergo conventional visual diagnostics: ophthalmic exam and visual function assessment (VFA). At 2y CA, VOF screening was repeated and neurodevelopment was assessed. Results 18 children (38%) were classified as at risk of VPD at 1y CA. 7 children had abnormal neurological signs, 5 had abnormal VOF, and 6 had both. Subsequent ophthalmic exams (N=14) showed severe hypermetropia in 21% and strabismus in 14%. VFA (N=10) showed abnormal visual function and behavior in only 1 child. At 2y CA, the total group showed an increase in abnormal VOF. Whereas the children at risk showed some normalization, the group without VPD risk at 1y CA showed deterioration of VOF. Neurodevelopmental outcome did not clearly differ between risk groups. Conclusions Our findings show a substantial risk of VPD during visual screening (in 38%) at 1y CA, but relatively few deficits on subsequent conventional ophthalmic exams and VFA. The data suggest that most conventional visual diagnostic methods at this young age are not related to the established VPD risks. VOF assessment should be used complimentary to Tthese methods should be used complimentary to VOF assessment. The fact that at 2y CA the number of children with a VPD risk based on abnormal VOF increased argues for more extensive and continuous screening in risk groups, at least until school age.